Microstructure evolution and dielectric properties of Ce-doped SrBi4Ti4O15 ceramics synthesized via glycine-nitrate process - Huiling Du; Cuiying Ma; Wuxiang Ma; Haiting Wang (Processing and Application of Ceramics, 2018)
Ce-doped strontium bismuth titanate (SrBi4Ti4O15, SBT) powders were prepared by glycine-nitrate process at 400–500 °C and the ceramics were sintered at 980 °C. The phase composition, morphology and electric properties were investigated. It was found that the calcined powders consist of a single phase SBT and the calcination temperature is lower than that for the conventional solid state method. The morphology of Cedoped SBT is flake-like and the layer size decreases with Ce-addition from 12 to 2 µm confirming that the addition of Ce3+ inhibits grain growth. The Curie temperature of Ce-doped SBT increased for about 20 °C compared to the pure SBT. The tan δ was ∼0.005 at 35 °C and even below 0.05 up to 400 °C. The temperature coefficient of dielectric constant was ∼0.012 and the rate of frequency change was 0.01–0.04, which indicated the high stability of dielectric properties of the Ce-doped SBT. Impedance analysis revealed that the conduction mechanism of the Ce-doped SrBi4Ti4O15 ceramics is mainly grain conduction.